Wingbeat frequency of some dipterans in Gorakhpur, Eastern Uttarpradesh - ISAAC L MATHEW,; DEEPAK SINGH, (International Journal of Pharma and Bio Sciences, 2017)
Insects with asynchronous flight muscles often have higher frequencies of wingbeat. Wingbeat frequency in dipterans reflects flight activity and efficiency by playing an important role of impacting longevity and fitness such as the ability of forage and hunt, compete for a mate and evade predators. The average wing beat frequencies during free flight of local Musca, Sarcophaga and Lucilia sp. were 261.75 ±4.41, 224.92±2.50 and 220.36±2.06 Hz respectively. Wingbeat frequency is a function of several factors like insect body weight, wing structure, age, metabolic status, locomotory requirements and ambient climatic factors. Thus, wingbeat frequency characteristics of an insect population can be indicative not only of these factors but also of noteworthy adaptive variation existing among populations.